Moderating Effects of Profitability on The Relationship between ESG Reporting and ‎Earnings Quality in African Manufacturing Firms - Akinadewo, Israel S.; Akinadewo , Jeremiah O.; Akinadewo, Elijah O. (International Journal of Accounting and Economics Studies, 2025)
This study examines the impact of Environmental, Social and Governance (ESG) reporting on ‎earnings quality of African listed manufacturing firms while adopting profitability, proxied by ‎Return on Assets (ROA) and Return on Equity (ROE), as a moderating variable. Adopting an ex ‎post facto research design and panel data of 49 firms over the period 2012-2023, the study ‎applies fixed-effects regression with robust standard errors to account for firm-specific ‎heterogeneity. It is found that the effect of ESG reporting on earnings quality is not uniform for the ‎three proxies: JMAQ, MJEQ, and DAEQ. Environmental reporting strengthens accruals ‎magnitude-based JMAQ, but weakens accrual-based MJEQ and DAEQ, emphasizing differences ‎between substantive and symbolic disclosure. The social and governance disclosures also have ‎mixed results, suggesting that the quality of disclosure is related to the genuineness of the practice ‎behind it. ROA exerts a positive impact on the quality of earnings in the ESG-earnings quality ‎relation in all firms, which implies that financially strong firms have greater potential to turn their ‎ESG engagements into believable reporting. On the other hand, ROE exhibits weaker and ‎inconsistent interaction effects. The study indicates the central importance of profitability in ‎determining whether ESG reporting will strengthen or weaken earnings quality for African ‎manufacturing firms and suggests that stronger governance monitoring, the convergence of ESG ‎disclosure standards, and the introduction of mandatory assurance regimes should be incorporated ‎moving forward to support credible sustainability reporting.
Keywords: Earnings Quality; ESG Reporting; Return on Assets; Return on Equity; Manufacturing Firms